Studi Kelayakan dan Profitabilitas Agroindustri Tahu: Perbedaan Pendapatan dari Kedelai Lokal dan Impor - Untari, Wiwik Sri; Fitriyaningsih, Fitriyaningsih; Muhlis, Abdullah (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2024)
Untari, W. S., Fitriyaningsih, F., Muhlis, A. (2024). Feasibility and profitability study of tofu agroindustry: differences in income from local and imported soybeans. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-12 Tahun 2024, Palembangg 21 Oktober 2024. (pp. 946–957). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Situbondo Regency is one of the areas that has the potential to become a tofu agro-industry production center because in several parts of the region the tofu agro-industry is spread. However, tofu made from imported soybeans is more popular with consumers than tofu made from local soybeans. The aimed of this research was to analyze the difference in income between the tofu agroindustry made from imported and local soybeans, as well as to analyze the feasibility of the imported and local soybean tofu agroindustry. For this reason, it is necessary to analyze the differences in income received by each agro-industry. The research area was determined deliberately (purposive sampling), namely 3 areas which are tofu production centers spread across Situbondo Regency with 50 tofu agro-industry respondents. The research methods used are descriptive and analytical methods. Data analysis used income difference analysis (t-test) and feasibility analysis (RC ratio). Research results 1) The tofu agro-industry made from local and imported soybeans, each obtains income that is greater than production costs. The average income received by the local soybean tofu agroindustry is IDR. 1,107,289.- /Day and imported soybean tofu agroindustry Rp. 1,985,152.- / Day, so that each tofu agroindustry is worth cultivating, the RC ratio value is > 1, namely 2 for the local soybean tofu agroindustry and 1.99 for the imported soybean tofu agroindustry. 2) There is a significant difference in income of 0.002603 between the local soybean tofu agroindustry and imported soybeans. The difference in income is due to the demand for tofu made from imported soybeans being higher than local soybeans, thus affecting the average income received. Apart from that, the price of imported soybean